False Transaction vs Wash Trading: Addressing the Gap to Rebuild Market Confidence (Legal Implication in Indonesia and United States Capital Market Law) - Sugianto, Fajar; Tokuyama, Shintaro (Universitas Negeri Semarang, 2024)
This paper is evidently about the legal comparison between Indonesia and the U.S on their views on market manipulation. There are several similarities between the Capital Market Law and SEA 1934, not only in terms but also in the elements. Articles 91 and 92 of Capital Market Law seem to mimic Section 9(a) (1) and (2) of SEA 1934. As both statues states similar prohibition in creating a misleading trading appearance and the purpose of inducing sales. This means that elements and tests applicable in the U.S. should also be applicable in Indonesia. Section 10(b) of SEA 1934 and SEC Rule 10b-5 serves to further supplement the application of Section 9 with its broad anti-manipulation provisions. Articles 91 and 92 of Capital Market Law cover the sales and purchase of stocks affected by the alleged manipulation that occurs only in the securities exchange as evident by the wording “on a/the Securities Exchange”. This is also observed in Section 9(a) (1) and (2) of SEA 1934 wherein the scope is limited to transactions in the “national securities exchange”. What this implies is that over-the-counter and block sales transactions are not protected under the statutes mentioned above. This issue is not addressed under the Capital Market Law, however Section 10(b) of SEA 1934 and its implementing regulation SEC Rule 10b-5 addresses this issue. Section 10(b) of SEA 1934 allows for broader authority of law enforcement as it includes “any security registered on a national securities exchange or any security not so registered”. This implies protection for a wider scope of securities transactions.